Identification of stripe rust resistance gene YrBDT in Chinese landrace wheat Baidatou using BSE-seq and BSR-seq - Jingchun Wu; Yukun Cheng; Weihao Hao; Bin Bai; Luping Fu; Yan Ren; Yuanfeng Hao; Ruiming Lin; Hongqi Si; Chuanxi Ma; He Zhonghu; Jiansheng Chen; et al. (Springer, 2024)
Stripe rust caused by Puccinia striiformis f. sp. tritici (Pst) is a devastating foliar disease of wheat. Chinese landrace wheat Baidatou has shown high resistance to a broad spectrum of Pst races at both the seedling and adult-plant stages for decades in the Longnan region of Gansu province, a hot spot for stripe rust epidemics. Here, we report fine mapping and candidate gene analysis of stripe rust resistance gene YrBDT in Baidatou. Analysis of F1, F2 plants and F2:3 lines indicated that resistance in Baidatou to Pst race CYR31 was conferred by a single dominant gene, temporarily designated YrBDT. Bulked segregant exome capture sequencing (BSE-seq) analysis revealed 61 high-confidence polymorphic SNPs concentrated in a 5.4-Mb interval at the distal of chromosome arm 6DS. Several SNPs and InDels were also identified by genome mining of DNA sampled from the parents and contrasting bulks. The YrBDT locus was mapped to a 943.6-kb (4,658,322–5,601,880 bp) genomic region spanned by markers STS2 and STS3 based on IWGSC RefSeq v2.1, including five putative disease resistance genes. There was high collinearity of the target interval among Chinese Spring RefSeq v2.1, Ae. tauschii AL8/78 and Fielder genomes. The expression level of TraesCS6D03G0027300 showed significant association with Pst infection, and a gene-specific marker CAPS3 developed from TraesCS6D03G0027300 co-segregated with YrBDT suggesting this gene as a candidate of YrBDT. The resistance gene and flanking markers can be used in marker-assisted selection for improvement of stripe rust resistance.